Diabetic ketoacidosis at type 1 diabetes onset: indirect impact of COVID-19 pandemic - Lazzeroni, Pietro; Bernardi, Luca; Pecora, Francesco; Motta, Matteo; Bianchi, Laura; Ruozi, Maria Beatrice; Giacometti, Alessandra; Venezia, Silvia; Dodi, Icilio; Iovane, Brunella (Acta Biomedica Atenei Parmensis, 2020)
Reorganization of healthcare resources due to COVID-19 pandemic has led to an unintentional neglect of essential care, especially for paediatric emergencies. This phenomenon has been observed also for type 1 diabetes patients at onset, and surveys from different countries have shown an increased number of diabetic ketoacidosis during lock-down period. We report the case of two patients admitted late at our emergency care service for type-1 diabetes at onset with ketoacidosis, for reasons related to COVID-19 pandemic outbreak. Case report 1: A 5 years old boy, presented with a severe diabetic ketoacidosis, requiring admission in Intensive Care Unit, prolonged intravenous insulin infusion and enteral nutrion via nasogastric tube. Case report 2:  A 10 years old girl presented in the emergency department with a history respiratory distress, due to Kussmaul's breathing, and severe dehydration. Laboratory findings were consistent with a diagnosis of moderate diabetic ketoacidosis. We have further analyzed the experience of our Centre regarding new onset type 1 diabetes patients during lock-down period: we observed a reduction of admissions for type 1 diabetes onset during lock-down period compared to same period of 2019, with a higher prevalence of moderate and severe diabetic ketoacidosis. We conclude highlighting the upcoming necessity, due to the emerging of a ‘second wave’ of the pandemic, that public opinion and healthcare practitioners provide correct information regarding access to paediatric services, in particular for children with newly onset symptoms, in order to avoid late access to emergency department in critical situations and to prevent avoidable morbidity and mortality.